2000
DOI: 10.1289/ehp.001081113
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the immune system associated with living near a pesticide dump site.

Abstract: In this paper, we report results of the second phase of a larger study designed to evaluate the effects on the immune system of living near a Superfund site containing organochlorine pesticides, volatile organic compounds, and metals. Phase II was conducted to determine whether living near the site, consisting of six locations in Aberdeen, North Carolina, is associated with higher plasma organochlorine levels, immune suppression, or DNA damage. Each of 302 residents of Aberdeen and neighboring communities prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 27 publications
1
19
0
2
Order By: Relevance
“…22 In New York City, particularly hazardous toxic waste sites have been designated New York State Superfund sites (NYC SFS) by the Department of Environment and Conservation (DEC). Deleterious effects on the immune system of individuals living near SFS have been reported by Vine et al, 23 and thyroid disease was increased among women living near SFS in NYS containing polychlorinated biphenyls. 24 Thus, we decided to determine if the prevalence of PBC is increased near NYC SFS employing data from several sources and multiple analytic methods.…”
mentioning
confidence: 85%
“…22 In New York City, particularly hazardous toxic waste sites have been designated New York State Superfund sites (NYC SFS) by the Department of Environment and Conservation (DEC). Deleterious effects on the immune system of individuals living near SFS have been reported by Vine et al, 23 and thyroid disease was increased among women living near SFS in NYS containing polychlorinated biphenyls. 24 Thus, we decided to determine if the prevalence of PBC is increased near NYC SFS employing data from several sources and multiple analytic methods.…”
mentioning
confidence: 85%
“…Prenatal exposure to DDT increases the risk of otitis media [35]; post-natal exposure to DDT has been linked to impairment of the upper respiratory tract immunity as evidenced by increased upper respiratory tract infections. It has been demonstrated that DDT diminished neutrophil functions and reduced mitogen-induced lymphocyte proliferation response [36]. On the other hand, a study enrolling children from Brazil exposed to DDT showed that the immune response to diptheria vaccine was not impaired [37].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…Metals, including lead, mercury, and cadmium, have also been reported in breast milk, but they do not usually accumulate to higher concentrations in breast milk than in blood. Chemical exposures to the mother may result from work, the ambient or home environment, diet, or carrying home of contaminants by another person living at the residence (Fenske 1997;Fingerhut et al 1991;National Research Council 1999;Rogan et al 1988;Vine et al 2000;Weisglas-Kuperus et al 2000).…”
Section: Compoundmentioning
confidence: 99%